Advances in 3D printed periodic lattice structures for energy research: Energy storage, transport and conversion applications - S.A. Khan (7943858) (2024)
Lattice structures, with their exceptional characteristics such as high specific strength and stiffness, thermal insulation, and biocompatibility, find a wide range of applications including bio-medical, thermal, automobile and aerospace industry. This study explores their potential for energy research, provides an overview of Periodic lattice structure (PLS) design and fabrication, and classifies them based on their energy function. It aims to provide insights into the potential applications, advancements, challenges, and future directions related to PLS implementation in energy research. The study categorized the recent advances and challenges of using PLS in energy conversion, storage, and transport applications and examines the challenges and limitations associated with them. The challenges and limitations include problems related to study design, reproducibility, sample sizes, multi-physics phenomena, integration with other energy storage components, interdisciplinary research, manufacturing accuracy, durability, scalability, and economic feasibility. Future research directions are suggested to address these challenges and opportunities, such as evaluating PLS performance on a broader scale, developing accurate modeling techniques, investigating underlying mechanisms, utilizing multi-physics modeling tools, examining long-term performance, exploring practical applications, and exploring alternative fabrication methods. Other Information Published in: Materials & Design License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matdes.2024.112773